Overcoming Hesitancy and Barriers to Care with Integration of Telemedicine in a Free Student-run Health Clinic - Vikki A. Krysov; Michelle E. Balshin; Elijah N. Azar; Karina Cernioglo; David Perekopskiy; Altynay T. Nurpeissova; Lucy Zhonglu Shi (Journal of Primary Care & Community Health)
Introduction: Nadezhda Clinic is a free student-run health clinic that provides culturally sensitive primary care services to the underserved Russian-speaking population of the greater Sacramento area. At the onset of the COVID-19 pandemic, the clinic suspended in-person services and solely offered telemedicine visits. Most patients were hesitant to utilize telemedicine due to poor technological literacy, privacy concerns, and a preference for in-person care. Objective: This quality improvement project aimed to evaluate whether the implementation of culturally sensitive telemedicine services and outreach strategies would help address patient hesitancy and barriers to care. Methods: Successful implementation of telemedicine was dependent on building trust with the community, providing multilingual technological assistance, and offering personalized support. Some measures that were reviewed in order to assess this included comparison of patient demographics, clinic attendance, and distance reached between in-person and telemedicine services. Results: Telemedicine implementation was associated with increased clinic attendance rates with a no-show rate as low as 13% when compared to in-person services with a no-show rate of 20%. Telehealth services also enabled the clinic to reach patients in rural areas up to 120 miles away. Conclusions: With the implementation of a culturally sensitive telemedicine protocol, Nadezhda Clinic achieved greater patient retention rates and reached patients at further distances, suggesting an overall reduction in hesitancy and barriers to care. Free clinics offering telemedicine are critical to further address healthcare disparities in marginalized communities.